2016
DOI: 10.3747/co.23.3404
|View full text |Cite
|
Sign up to set email alerts
|

Early Integration of Palliative Care into Standard Oncology Care: Evidence and Overcoming Barriers to Implementation

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…In the NL, a recent study showed that GPs were more hesitant to engage in ACP with patients who were still being treated by specialists in hospital, as these patients are often less open to discussion 33. Numerous initiatives have been developed to make earlier integration of specialised palliative care services a reality 34–37. Consequently, certain topics may be more frequently discussed with palliative caregivers or nurses of the palliative homecare team rather than with GPs.…”
Section: Discussionmentioning
confidence: 99%
“…In the NL, a recent study showed that GPs were more hesitant to engage in ACP with patients who were still being treated by specialists in hospital, as these patients are often less open to discussion 33. Numerous initiatives have been developed to make earlier integration of specialised palliative care services a reality 34–37. Consequently, certain topics may be more frequently discussed with palliative caregivers or nurses of the palliative homecare team rather than with GPs.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence indicates that timely referral into palliative care services has a positive impact on quality of life and can reduce hospitalisation and symptom burden [46] but research in this area is largely North American [47,48] or Japanese [49] and mainly relates to patients with cancer. Exceptions to this include investigative studies into symptom focused interventions for conditions such as breathlessness [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits for oncology patients and their families of early introduction of palliative care are believed to substantially outweigh the potential ramifications 6,7 . In addition, early implementation of palliative care can aid in providing individualized and effective care for the patient, which promotes patient satisfaction and fulfils their needs 6,8 . Palliative management also proves suitable in various neurosurgical conditions, including traumatic head injuries, massive intracranial hemorrhages, and brain tumours 3 .…”
Section: Introductionmentioning
confidence: 99%